Age and Social Status at Marriage: (The Pakistan Development Review, 1965)
Prior to July 15, 1961, when the Muslim Family Laws Ordinance [5] came into effect, formal registration of marriages was not required, although a record of marriages was usually kept by the person performing the ceremony (Qazis, Mosque Imams, etc.). However, no centralized system of registration of marriages existed, with the result that no reliable statistics concerning marriages in Pakistan were available. For all practical purposes, all Muslim and Hindu marriages in Pakistan are arranged by the two families. But since 1961 the registration of marriages has been required, and, as the law applies only to Muslims, the followers of Islam are expected to adhere to it. At a later date, perhaps, members of other religious communities may also be required to register their marriages. Karachi, the major commercial and industrial city of the nation, as well as its most populous city, is 96.9 per cent Muslim [7, Vol. 1, Part II, p. 60]. The administration of the Family Laws Ordinance is left in the hands of the Basic Democrats Union Committees, and the registration of marriages, as well as other official business is conducted in the Basic Democrats' Union offices. The city is divided into a number of registration areas, and, although it is possible to register marriages elsewhere, residents normally record their intentions at the local union office in the registration area where the bride resides.